Economic-analytical models for diagnosing the productivity of construction development enterprises - Gergi, Denys; Demchuk, Andrii; Koshelnyi, Ivan; Buniak, Serhii; Petrenko, Oleksandr (Ways to Improve Construction Efficiency, 2022)
The article develops an integrated framework of economic-analytical models for diagnosing the productivity of construction development enterprises, tracing the evolution from index-based and production-function measurements to digitalized, risk-adjusted and ESG-oriented systems. It substantiates that a developer’s productivity is shaped not only by on-site parameters but primarily by the duration and controllability of the entire cycle “land → design/permits → construction → sales/operation,” where capitalization speed and market absorption rate are pivotal. At the theoretical level, it clarifies the continuum “operational efficiency — effectiveness — productivity” and their measurement demarcation: from resource return (output/input) and total factor productivity (TFP) to multi-criteria panels (BSC/MCDA) integrating time, financial, quality, and client-oriented indicators. Methodologically, it outlines the shift from project controlling (EVM, PERT/CPM) and comparative efficiency (DEA/SFA, Malmquist TFP) to BIM-integrated 4D/5D models, process mining of ERP/BIM events, and digital twins enhanced with ML/AI forecasting. The study proposes interpreting productivity as a risk- and ESG-adjusted magnitude that combines “cash-in-time productivity,” schedule/quality variability (robust/CVaR metrics), and carbon-energy indicators (m² per t CO₂e, EBITDA energy intensity). Practical value lies in roadmaps for selecting models across managerial horizons: operational (EVM + Lean KPI), tactical (DES/process-mining for approval and logistics bottlenecks), and strategic (portfolio-level digital twin with scenario-based NPV/IRR and ESG constraints). The results can be applied to standardize productivity management systems in development companies, support early detection of delay risks, and optimize project portfolios considering capital, demand, and regulatory conditions.